2013
DOI: 10.1016/j.jbankfin.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Rewards for downside risk in Asian markets

Abstract: Distributional properties of emerging market returns may impact on investor ability and willingness to diversify. Investors may also place greater weighting on downside losses, compared to upside gains. Using individual equities in a range of emerging Asian markets, we investigate the potential contribution of downside risk measures to explain asset pricing in these markets. As realized returns are used as a proxy for expected returns, we separately examine conditional returns in upturn and downturn periods, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…Many studies on developed and emerging markets showed that downside measures better explain variability in the cross-section of returns than conventional ones (Estrada, 2002(Estrada, , 2007Post & van Vliet, 2006). The studies using individual securities also demonstrate that downside risk measures better explain securities returns than the beta coefficient (Alles & Murray, 2013;Pedersen & Hwang, 2007). Ang, Chen, & Xing (2006), based on companies listed on the NYSE, AMEX and NASDAQ, showed that investors are rewarded with a market premium for the downside risk, which means that the assets with higher downside beta coefficients reach higher rates of return on average.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies on developed and emerging markets showed that downside measures better explain variability in the cross-section of returns than conventional ones (Estrada, 2002(Estrada, , 2007Post & van Vliet, 2006). The studies using individual securities also demonstrate that downside risk measures better explain securities returns than the beta coefficient (Alles & Murray, 2013;Pedersen & Hwang, 2007). Ang, Chen, & Xing (2006), based on companies listed on the NYSE, AMEX and NASDAQ, showed that investors are rewarded with a market premium for the downside risk, which means that the assets with higher downside beta coefficients reach higher rates of return on average.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The regressions are estimated each month over the time period July 1996 through August 2014. 17 Pettengill et al (1995), Ang, Chen, and Xing (2006), and Alles and Murray (2013) show that risk premium is affected by market return. They define the sample upturn and downturn markets and report different predictability of betas among these samples.…”
Section: Return Predictability Of Skewness; the Effect Of Market Rementioning
confidence: 99%
“…Porównania wyceny aktywów za pomocą klasycznych i dolnostronnych współczynników beta dokonywano na wielu rozwiniętych i rozwijających się rynkach kapitałowych. Badania przy użyciu szeregów indywidualnych stóp zwrotu na europejskich oraz azjatyckich giełdach pokazały, że ryzyko dolnostronne wyjaśnia poziom stóp zwrotu u większej części walorów niż klasyczne miary ryzyka (Pedersen, Hwang, 2007;Artavanis, Diacogiannis, Mylonakis, 2010;Alles, Murray, 2013;Markowski, 2013).…”
Section: Wprowadzenieunclassified